Multiple outputs queue switching for detection of faulty of pilot cable by using pulsed technique: article - Azhari, Azhari (2004)
This paper develops the implementation of technique to control the inspection wires in pilot cable by using multiple output queued switch. This MOQ switching has a selector that sorts the multiple outputs switching to connect the specific input to the single output. This project used a pulsed signal as the signal source where it is used to transmit in the pilot cable wires which mostly placed underground and the oscilloscope used as a waveform monitor. This idealized switching is available to modified input voltage of TDR at any value and easy to carry out any where. A computer program is developed so that it can transfer all the data that appeared on the oscilloscope and straightly save in computer. As a result, the analysis of the data which is reflected waveform can easily be performed. The software called Labview was chosen to apply for this programming. This MOQ switching is implemented to use as tester switch for low-voltage and high-voltage circuit.